Strategi Komunikasi Bisnis Di Era Digital Perspektif Etika Komunikasi Bisnis Islam - Hermawati, Puput Aprilia; Rosyidi, Imron (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study aims to understand Islamic business communication ethics and business strategies in Islam. The research employs a qualitative approach using a descriptive method. The results of the study indicate that the first principle to be considered in business from an Islamic perspective is tawhid (monotheism). Humans must lead in managing existing resources and technology in the best possible way as part of their duties. Additionally, Islamic business ethics are based on principles of balance and justice, which refer to a broad concept related to almost all aspects of social, political, and economic life. The reference for Islamic business communication strategies lies in the application of media digitalization in Islamic businesses, implemented through strategies widely adopted by entrepreneurs and SMEs just starting their businesses digitally.